Expression of DNA repair proteins hMSH2, hMSH6, hMLH1, O6-methylguanine-DNA methyltransferase and N-methylpurine-DNA glycosylase in melanoma cells with acquired drug resistance - Lage, Hermann; Schadendorf, Dirk (International journal of cancer, 1999)
Malignant melanoma is well known for its primary unresponsiveness to chemotherapy. The mechanisms conferring this intrinsic resistance are unclear. In this study, we investigated the role of genes involved in DNA repair in a panel of human melanoma cell variants exhibiting low and high levels of resistance to 4 commonly used drugs in melanoma treatment, i.e., vindesine, etoposide, fotemustine and cisplatin. We show that in melanoma cells exhibiting resistance to cisplatin, etoposide and vindesine, the nuclear content of each of the DNA mismatch repair (MMR) proteins hMLH1, hMSH2 and hMSH6 was reduced by 30-70%. A decreased expression level of up to 80% of mRNAs encoding hMLH1 and hMSH2 was observed in drug-resistant melanoma cells selected for cisplatin, etoposide and fotemustine, while vindesine-selected cells showed only moderate reduction. In melanoma cells that acquired resistance to fotemustine, the amount of nuclear MMR proteins was nearly unaltered, whereas the activity of O6-methylguanine-DNA methyltransferase (MGMT) was considerably enhanced. Activity of N-methylpurine-DNA glycosylase (MPG) was not significantly altered in any of the drug-resistant melanoma cells. Our data indicate that modulation of both MMR components and MGMT expression level may contribute to the drug-resistant phenotype of melanoma cells. Int. J. Cancer 80:744-750, 1999. © 1999 Wiley-Liss, Inc.